1979
DOI: 10.1056/nejm197906143002404
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Specialists to the Delivery of Primary Care

Abstract: Despite increased numbers of medical-school graduates and opportunities for "primary-care" specialty training since the mid-1960's, many believe that the shortage of physicians delivering generalist care will continue through the 1980's. Missing, however, is solid information on the role of physician specialists in providing such care. Two national studies have shown that one of every five Americans now receives continuing general medical care from a specialist physician. Our study suggests that, despite the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(63 citation statements)
references
References 7 publications
0
62
0
1
Order By: Relevance
“…13 Aiken, et al, using data from the Mendenhall study,4 concluded that subspecialty internists are a major source of primary care services. 2 Spiegel, et Although a number of previous studies have described how physicians counsel patients, they either did not focus on differences between generalists and subspecialists or they were conducted prior to the 1970s, when the current concept of the general internist reemerged.5-'4 In this article, we evaluate the practices of general and subspecialty internists in counseling patients about cigarette smoking and regular exercise, using data from the Physician Practice Study. '5 internists practice tertiary prevention by counseling a high percentage of smokers with heart or lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…13 Aiken, et al, using data from the Mendenhall study,4 concluded that subspecialty internists are a major source of primary care services. 2 Spiegel, et Although a number of previous studies have described how physicians counsel patients, they either did not focus on differences between generalists and subspecialists or they were conducted prior to the 1970s, when the current concept of the general internist reemerged.5-'4 In this article, we evaluate the practices of general and subspecialty internists in counseling patients about cigarette smoking and regular exercise, using data from the Physician Practice Study. '5 internists practice tertiary prevention by counseling a high percentage of smokers with heart or lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable overlapping of roles of general practitioners giving specialized care and specialists providing general practice services, the so called "hidden primary care" (100,101), further complicating the comparability of research findings in different countries and contexts.…”
Section: What Are the Advantages And Disadvantages Of Restructuring Amentioning
confidence: 99%
“…[14][15][16][17][18] If a patient split his or her visits equally between 2 physicians, the physician with the highest total charges was designated as the principal-care physician.…”
Section: Principal-care Practitionermentioning
confidence: 99%
“…[34][35][36][37] Our definition of the principal-care physician has the advantage of conceptual simplicity and a lack of ambiguity. [14][15][16][17] We tested the robustness of the relationship between having a principal-care physician and a lower likelihood of having an emergency department visit by restricting our analysis to different patient subsets-patients with a minimum number of visits, patients with different disease burdens-and by varying the functional form of the independent variable.…”
Section: Limitationsmentioning
confidence: 99%